2018
DOI: 10.1038/s41598-018-23109-8
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoinositides regulate the TCR/CD3 complex membrane dynamics and activation

Abstract: Phosphoinositides (PIs) play important roles in numerous membrane-based cellular activities. However, their involvement in the mechanism of T cell receptor (TCR) signal transduction across the plasma membrane (PM) is poorly defined. Here, we investigate their role, and in particular that of phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] in TCR PM dynamics and activity in a mouse T-cell hybridoma upon ectopic expression of a PM-localized inositol polyphosphate-5-phosphatase (Inp54p). We observed that dephosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 71 publications
4
37
0
1
Order By: Relevance
“…). By modifying the local interaction with the cortical cytoskeleton, they change the mechanical stability and the dynamic of proteins in the membrane . Modifications of the lipid composition can also change the curvature of the membrane and favor membrane fusion …”
Section: New Hypotheses About the Function Of Vesicular Pools Of Tcr mentioning
confidence: 99%
“…). By modifying the local interaction with the cortical cytoskeleton, they change the mechanical stability and the dynamic of proteins in the membrane . Modifications of the lipid composition can also change the curvature of the membrane and favor membrane fusion …”
Section: New Hypotheses About the Function Of Vesicular Pools Of Tcr mentioning
confidence: 99%
“…Reduction in PI(4,5)P2 at the cSMAC would prevent actin recruitment and thus allow proper recruitment and secretion of cytotoxic granule . Finally, ectopic expression of the PI(4,5)P2 phosphatase Inp54p at the PM reduced the inner leaflet electrostatic membrane potential and induced CD3ε dissociation as well as increased CD3ζ phosphorylation after pMHC engagement …”
Section: Modulation Of Electrostatic Interactions In Immune Receptor mentioning
confidence: 99%
“…Considering the PI(4,5)P2 engine model, more clear possibility is that the increase in the amount of PI(4,5)P2 at the plasma membrane by PIP5K overexpression, will likely enhance more PI(4,5)P2 inside of the T cell microclusters, which could jam the engine (signaling microcluster). In contrast, the PI(4,5)P2 deletion restricted to the Lck 1‐12 ‐localized region augmented the TCR signaling . The report speculated that it may be due to the unbinding or CD3ε cytoplasmic domain from the inner leaflet of plasma membrane .…”
Section: A Pi(45)p2‐derived “Gasoline Engine Model” For the Sustainementioning
confidence: 96%
“…And the PI(4,5)P2 dephosphorylation by the expression of Inp54p augments the constitutive and antigen‐elicited CD3 phosphorylation as well as the antigen‐stimulated early TCR signaling pathways. Further study showed that PI(4,5)P2 depletion strongly promotes the CD3ε cytoplasmic domain dissociation from the inner leaflet of plasma membrane in live cells, thus resulting in an increased CD3 availability for interacting with Lck . Considering the PI(4,5)P2 engine model, more clear possibility is that the increase in the amount of PI(4,5)P2 at the plasma membrane by PIP5K overexpression, will likely enhance more PI(4,5)P2 inside of the T cell microclusters, which could jam the engine (signaling microcluster).…”
Section: A Pi(45)p2‐derived “Gasoline Engine Model” For the Sustainementioning
confidence: 99%